School lessons, social media and political events in a get-out-the-vote campaign: successful drivers of political engagement among youth?. (8th August 2020) - Ohme, Jakob; Marquart, Franziska; Kristensen, Lisa Merete
ABSTRACT: During election times, societal actors frequently employ specific get-out-the-vote campaigns to mobilize young voters' turnout and engagement with the election. Although such campaigns receive praise in society, little is known about how effective they are and if they shape longer lasting types of political engagement. This study presents novel evidence about the differential effects of a multi-platform get-out-the-vote campaign in Denmark, and investigates how such campaigns can help to address the important democratic problem of youth disengagement. Based on a two-wave panel study among high school- and university students in Denmark ( n = 275), the effects of classroom interventions, political event participation, and social media use on political interest, knowledge, and political efficacy are explored. The results suggests that get-out-the-vote campaigns are able to strengthen youths' political engagement, but that civic education and political events may be more important than communication via social media.